CLINICAL CASE OF GUILLAIN-BARRE SYNDROME ON THE BACKGROUND OF ECLAMPSIA IN A PREGNANT WOMAN - Пеганова, Марина Анатольевна; Филимонов, Сергей Николаевич; Пеганов, Анатолий Игоревич; Полукарова, Елена Алексеевна; Чеченин, Андрей Геннадьевич (Medicine in Kuzbass, 2020)
Subject of research. Study of the influence of pathogenic factors and predisposing conditions on the development of Guillain-Barré syndrome. Purpose of research – demonstration of a clinical case of Guillain-Barré syndrome in a pregnant woman. Results. The background and possible provoking factors of the disease were: the third trimester of pregnancy, accompanied by late toxicosis and severe edema, the presence of sinusitis and antibodies to Epstein-Barr virus, cytomegalovirus, and herpes simplex virus detected during serological studies. Application. Neurology, obstetrics, therapy, diagnosis and treatment of Guillain-Barré syndrome. Conclusion. The background and possible provoking factors of the disease were: the third trimester of pregnancy, accompanied by late toxicosis and severe edema, sinusitis, and antibodies to Epstein-Barr virus, cytomegalovirus, and herpes simplex virus detected during serological examination.